Computers as stepping stones?: technological change and equality of labor market opportunities - Arntz, Melanie; Vom Berg, Cäcilia; Neidhöfer, Guido; Zierahn-Weilage, Ulrich (Discussion paper, 2022)
This paper analyzes whether technological change improves equality of labor market opportunities by decreasing returns to parental background. We find that in Germany during the 1990s, computerization improved the access to technologyadopting occupations for workers with low-educated parents, and reduced their wage penalty within these occupations. We also show that this significantly contributed to a decline in the overall wage penalty experienced by workers from disadvantaged parental backgrounds over this time period. Competing mechanisms, such as skill-specific labor supply shocks and skill- upgrading, do not explain these findings.